Disseminated cutaneous‐only histoplasmosis in a patient with AIDS. (28th June 2019) - Lin, Matthew J; Mazzoni, Daniel; Gin, Douglas
Abstract: Histoplasmosis is an opportunistic fungal infection that occurs predominantly in immunocompromised patients. Cutaneous lesions in histoplasmosis are rare and typically occur in the absence of extra‐cutaneous manifestations. We present a rare case of disseminated cutaneous‐only histoplasmosis in a patient with recently diagnosed AIDS.